Development and Validation of an Assessment Instrument for Mentoring and Technical Assistance Skills of Master Teachers - Gungon, Sharon R.; Biray, Ersyl T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Master teachers in the Philippines play a vital role in guiding and supporting fellow teachers through mentoring, coaching, and providing technical assistance; thus, they are expected to remain updated and skilled to effectively help colleagues meet classroom challenges. Since no standardized instrument currently exists to measure their skills, this study designed a validated tool that would accurately evaluate these. This mixed-method study utilizing the exploratory sequential design involved 17 participants for the qualitative phase, and a larger group of respondents for the quantitative phase. In the qualitative phase, teacher-mentees shared their experiences and described how master teachers provide mentoring and technical assistance. These insights served as the foundation for developing the initial items of the instrument. In the quantitative phase, the crafted tool underwent Rasch analysis to test its reliability and validity. The results showed acceptable levels of reliability (person reliability = 0.84; item reliability = 0.97) and validity (variance explained = 62.5%; CVI = 0.96; Infit/Outfit MNSQ = 0.54–1.14), confirming that the instrument effectively measured the intended constructs. The findings suggest that the developed MenTeASk Questionnaire was both valid and reliable in assessing the master teachers’ mentoring and technical assistance skills; hence, its use is recommended particularly in the Division of Aklan, Philippines.